Efficacy and safety of a thermosensitive hydrogel for endoscopic submucosal dissection: An in vivo swine study. - Han Jo Jeon; Hyuk Soon Choi; Eun Ju Bang; Kang Won Lee; Sang Hyun Kim; Jae Min Lee; Eun Sun Kim; Bora Keum; Yoon Tae Jeen; Hong Sik Lee; Hoon Jai Chun; Seung Jeong; et al. (PLoS ONE, 2021)
Injectable thermo-sensitive chitosan hydrogels have recently been developed for the use of submucosal fluids in endoscopic submucosal dissections (ESD). This study aimed to investigate the efficacy and safety of chitosan hydrogels during ESD. Submucosal fluids were administered as follows: 0.9% normal saline (NS), 0.4% hyaluronic acid (HA) and chitosan/β-glycerophosphate (CS/GP) hydrogel. Each solution was administered twice into the stomach and colon of a pig, with a total of 72 ESD procedures performed on 12 pigs. The injected volume and procedure-related parameters were recorded and analyzed. ESDs that created ulcers after 7 days were histologically compared. All ESD specimens were resected en bloc. The total injected volumes during ESD of the stomach (NS, 16.09±3.27 vs. HA, 11.17±2.32 vs. CS/GP, 9.44±2.33; p<0.001) and colon (NS, 9.17±1.80 vs. HA, 6.67±1.50 vs. CS/GP, 6.75±1.57; p = 0.001) were significantly different. Hydrogel showed significant differences from normal saline in terms of fluid power (mm2/vol; NS, 35.70±9.00 vs. CS/GP 57.48±20.77; p = 0.001) and consumption rate (vol/min; NS, 2.59±0.86 vs. CS/GP, 1.62±0.65; p = 0.013) in the stomach. Histological examination revealed preserved muscularis propria, although the chitosan hydrogel resulted in a partial inflammatory response, with a hypertrophied submucosal layer. Chitosan hydrogel was found to be superior to normal saline, with an efficacy similar to that of hyaluronic acid. Nonetheless, long-term histological changes should be evaluated before clinical implementation.